PENGARUH MANAJEMEN KELAS TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 TANJUNG RAJA - Sapta Melinda; Siti Fatimah; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This study aimed to prove the effect of Classroom Management on Student Learning Motivation on Economics Subjects in SMA Negeri 1 Tanjung Raja. The Population of this study ware all classes X IIS in SMA Negeri 1 Tanjung Raja. The Sample of this study ware 28 students of X IIS class as the experimental grup chosen by using Cluster Random Sampling. To collect the data, observation, questionnaires and interview were used. Technique analysis of observation data using the formula percentage, obtained grade management average 93.75%. Technique of analysis of questionnaire data obtained by 70,40% with good criterion.Hypothesis test results obtained Fhitung ≥ Ftabel or 25.18 ≥ 4.22. This indicates that there is influence of classroom management on learning motivation of learners on economic subjects in SMA Negeri 1 Tanjung Raja. From the results of this study, teacher have to be moreunderstand of learning condition which is not optimal yet, in accordance with the situation in the process of learning in the classroom, so that learners are more interested in learning